Cigarette smoke affects the onco-suppressor DAB2IP expression in bronchial epithelial cells of COPD patients - Anzalone, Giulia; Arcoleo, Giuseppe; Bucchieri, Fabio; Montalbano, Angela M.; Marchese, Roberto; Albano, Giusy D.; Di Sano, Caterina; Moscato, Monica; Gagliardo, Rosalia; Ricciardolo, Fabio L. M.; Profita, Mirella (Scientific reports, 2019)
Cigarette smoke is a risk factor for COPD and lung cancer. In cancer, epigenetic modifications affect the expression of Enhancer of Zester Homolog 2 (EZH2), and silenced disabled homolog 2 interacting protein gene (DAB2IP) (onco-suppressor gene) by Histone H3 tri-methylation in lysine 27 (H3K27me3). In“ex vivo” studies, we assessed EZH2, H3K27me3 and DAB2IP immunoreactivity in bronchial epithelial cells from COPD patients (smokers, ex-smokers), Smoker and control subjects. In “in vitro” experiments we studied the effect of cigarette smoke extract (CSE) on EZH2/H3K27me3/DAB2IP expression, apoptosis, invasiveness, and vimentin expression in 16HBE, primary cells, and lung cancer cell lines (A549) long-term exposed to CSE. Finally, in “i n vitro”studies , we tested the effect of GSK343 (selective inhibitor of EZH2). EZH2 and H3K27me3 expression was higher, while DAB2IP was lower levels, in bronchial epithelium from COPD and Smokers than in Controls. CSE increased EZH2, H3K27me3 expression and decreased DAB2IP, cell apoptosis and invasiveness in epithelial cells. GSK343 restored the effects of CSE. Cigarette smoke affects EZH2 expression, and reduced DAB2IP via H3K27me3 in COPD patients. The molecular mechanisms associated with EZH2 expression, generate a dysregulation of cell apoptosis, mesenchymal transition, and cell invasiveness in bronchial epithelial cells, encouraging the progression of airway inflammation toward lung cancer in COPD patients.